Modernization and Local Wisdom in the Agricultural System: The Case of Samin Indigenous Community in Baturejo Village, Pati Regency, Central Java - Windi Mayang Sari; Rina Mardiana; Bayu Eka Yulian (Sodality: Jurnal Sosiologi Pedesaan, 2024)
Agricultural modernization is a change in agricultural patterns from traditional to modern methods. The Samin Indigenous Community is one whose main livelihood depends on agriculture. This study aims to analyze the existence of the local wisdom of the Samin Indigenous Community in Baturejo Village, Sukolilo District, and Regency in the current agricultural modernization. This study used mixed methods and a combination of qualitative and quantitative methods. Qualitative data were obtained by conducting in-depth interviews with informants selected by snowball sampling, observation, and documentation. Quantitative data were obtained using a survey method for 30 respondents selected by accidental sampling. The encounter between agricultural modernization and local wisdom creates three conditions for the local wisdom of samin farming: local wisdom that faded existence, local wisdom that disappeared, and local wisdom that adapted so that it went hand in hand with agricultural modernization. Some of Samin's local wisdom still exists in the midst of agricultural modernization driven by several factors, such as the pride of the Samin community in their identity, the transfer of cultural knowledge to the younger generation, the traditional attitude of the Samin community, and the low use of information and communication technology.